Adult learner : strategies for success - Steinbach, Robert L. (Crisp Pub. Menlo ParkUS, 1993)
Caters for adult learners and proposes the ASK (actively seek knowledge) attitude as the key to successful life-long learning. Explores individual learning styles; focuses attention on the significance of listening to learning; and discusses the usefulness of high-tech learning tools viz. audiotapes, videotapes, videodiscs, and computers. Provides a four-step process for improving reading comprehension, and advises on maximising memory potential.